The Effect of Low-Density Poly Ethylene (LDPE) Towards Plastic Oil Quality - Hariadi, Dedy; Yamin, R. Anwar; Aprilia, Sri; M. Saleh*, Sofyan (Aceh International Journal of Science and Technology, 2021)
Nowadays, the use of plastics is inseparable from daily life activities for both industrial commercial and household needs. Every year, an average individual consumes 700 plastic bags. Furthermore, the major types of plastic pollutants are High Density Polyethylene (HDPE) and Low Density Polyethylene (LDPE). The nature of LDPE plastic makes it very difficult to undergo decomposition. Subsequently, efforts to overcome this problem have been carried out by several methods of processing or utilizing its waste through pyrolysis. This s tudy aims to determine the effect of the quality of LDPE plastic waste on the plastic oil produced from the pyrolysis process. Based on their chemical compounds, all plastic oils produced were categorized as carbon compounds instead of hydrocarbons. Althou gh, from the quality of the LDPE plastic used, the process produced gasoline, naphtha, and kerosene, the quality of each oil was different. Therefore, the higher the quality of the LDPE plastic used, the better the quality of the oil produced.